Eco-friendly surfactant to demulsification water in oil emulsion: synthesis, characterization and application - Saad, M.A.; N. H., Abdurahman; Rosli, Mohd Yunus (Elsevier, 2020)
The need to replace of petroleum-based oil field chemicals with materials sourced from natural products has received significant attention owing to the eco-friendliness of these nature-based materials. In this study, we focused on the synthesis of a surfactant for use as a demulsifier for a water-in-oil emulsion. The demulsifier was synthesised via conden- sation reactions of corn oil with diethanolamine in the presence of a catalyst. The sur- factant was characterised by FTIR, NMR, and GC–MS analyses. The separation efficiency of the surfactant was studied using bottle tests. The water separation from the emulsion 97% was achieved. The influence of the concentration and settling time on the demulsification efficiency was investigated. The result showed that increasing the concentration and set- tling time resulted in increased separation efficiency of the emulsion. The results of this investigation demonstrated the suitability of using corn oil in the synthesis of a surfactant as a demulsifier for crude oil emulsion. Nevertheless, more investigations are required to determine the mechanisms to optimise the system for industrial applications.